Panel Data Regression Analysis with GLMM Approach (Case Study: HDI in South Sulawesi Province) - Adiatma Adiatma; Adnan Sauddin; A. Hikmawati (Bulletin of Economic Studies (BEST), 2021)
South Sulawesi is a province consisting of several regencies/cities. To understand well the HDI of South Sulawesi, it takes a good understanding of the HDI situation of each Regency/City. The HDI situation which continues to increase from year to year can be used as an indicator to measure success in human development efforts. HDI can also determine the ranking or level of development of a region/country. This study aims to determine the factors that have a significant effect on HDI and to find out the best panel data regression model for HDI in South Sulawesi. The method used in this study is panel data regression analysis with the Generalized Linear Mixed Model (GLMM) approach. The results showed that the variable life expectancy (AHH), average length of school (RLS) and per capita expenditure (PP) had a significant effect on the human development index (HDI) in South Sulawesi Province in 2014-2018.Keywords: HDI, Panel Data Regression, Generalized Linear Mixed Model.